PERBANDINGAN KINERJA PERUSAHAAN SEBELUM DAN SESUDAH MERGER PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hariyanti Hariyanti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aimed to analyze the company's performance before and after the merger are listed on the Indonesia Stock Exchange. Financial performance is measured using financial ratios, namely: current ratio, total asset turnover, debt to total assets, operating profit margin, return on investment, return on equity, and stock return around the announcement of the merger. Merger is a merger of two or more companies into one force to strengthen the company's position. In this study, the data used is secondary data. While the population of this study included a public company listed on the Stock Exchange were once merged, and the company announced that its activities in the period 2000-2004. The sampling method used in this research is purposive sampling, there are 20 companies included in the research criteria. Data analysis techniques used to answer the hypothesis is using parametric statistical tests two different test average by using the t test. The results of the analysis proves that the current ratio, total asset turnover, debt to total assets, net profit margin, return on investment and return on equity increased while operating profit margin declined after the merger. Stock returns before and after the merger increases, it is evident after the merger the share price increased and a significant influence on the company's performance